Cardiotoxicity Assessment of EGFR Tyrosine Kinase Inhibitors Using Human iPS Cell‐Derived Cardiomyocytes and FDA Adverse Events Reporting System - Shota Yanagida; Hiroyuki Kawagishi; Mitsuo Saito; Hirofumi Hamano; Yoshito Zamami; Yasunari Kanda (Clinical and Translational Science)
ABSTRACT Recent advances in the development of anti‐cancer drugs have contributed to prolonged survival of cancer patients. In contrast, drug‐induced cardiotoxicity, particularly cardiac contractile dysfunction, is of growing concern in cancer treatment. Therefore, it is important to understand the risks of anti‐cancer drug‐induced cardiac contractile dysfunction in drug development. We have previously developed image‐based motion analysis using human induced pluripotent stem cell‐derived cardiomyocytes (hiPSC‐CMs) to assess the effect of drugs on contractility. However, the utility and predictive potential of image‐based motion analysis using hiPSC‐CMs for anti‐cancer drug‐induced cardiac contractile dysfunction have not been well understood. Here we focused on epidermal growth factor receptor (EGFR)‐tyrosine kinase inhibitors (TKIs) and investigated the correlation between the hiPSC‐CMs data and clinical signals of adverse events related to cardiac contractile dysfunction. We examined the effects of the four EGFR‐TKIs, osimertinib, gefitinib, afatinib, and erlotinib, on the contractility of hiPSC‐CMs using image‐based motion analysis. We found that osimertinib decreased contraction velocity and deformation distance in a dose‐ and time‐dependent manner, whereas gefitinib, afatinib, and erlotinib had little effect on these parameters. Next, we examined the real‐world data of the EGFR‐TKIs using FDA Adverse Event Reporting System (FAERS; JAPIC AERS). Only osimertinib showed significant clinical signals of adverse events related to cardiac contractile dysfunction. These data suggest that hiPSC‐CM data correlate with clinical signals in FAERS analysis for four EGFR‐TKIs. Thus, image‐based motion analysis using hiPSC‐CMs can be a useful platform for predicting the risk of anti‐cancer drug‐induced cardiac contractile dysfunction in patients.